2015
DOI: 10.1016/j.jsurg.2014.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Medical Students’ Comfort Levels With Performing the Basic Head and Neck Examination in Practice: Follow-up During the Core Clerkship Year

Abstract: The initial teaching session persistently improved medical students' comfort levels in performing the H&NPE, with some attrition in comfort levels with performing the nasal examination and complete H&NPE. An otolaryngologist-directed, practical educational intervention may permanently reinforce the acquisition of complex skills such as the H&NPE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Authors suggested that otolaryngologists assist with experiential teaching through dissection and provide didactic lectures to increase students' exposure to specialists. A 2015 US study evaluated second‐year medical students' comfort levels with performing head and neck examination, and found that instruction improved comfort, although this diminished at 1 year for the nasal examination. A third US study of nine medical students and nine junior residents found that three‐dimensional educational modules were effective in teaching spatial orientation and sinus and skull base anatomy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors suggested that otolaryngologists assist with experiential teaching through dissection and provide didactic lectures to increase students' exposure to specialists. A 2015 US study evaluated second‐year medical students' comfort levels with performing head and neck examination, and found that instruction improved comfort, although this diminished at 1 year for the nasal examination. A third US study of nine medical students and nine junior residents found that three‐dimensional educational modules were effective in teaching spatial orientation and sinus and skull base anatomy.…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen articles discussed educational methods. Most found that clinic‐based teaching was highly rated by students, as was small group instruction.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests a need for widespread evaluation of the medical school curriculum. 15,17,18 We sought to assess medical students' perceptions of ophthalmology training at New York University School of Medicine (NYUSOM), where there is no mandatory ophthalmology clinical rotation. Similar to many other schools, NYUSOM currently trains students in clinical ophthalmology skills during preclinical years, has a student interest group, and offers an optional clinical rotation but does not require one.…”
mentioning
confidence: 99%
“…But besides these teaching peculiarities, our practical training is programmed and coordinated with the theoretical contents, in the same way as it should be done in any other subject. The peculiarity resides in the fact that in these practical activities we use models (dissected corpses, plastinated corpses or materials and plastic commercial models) that need to be thoroughly defined and discussed [7,9,10]. During the activities, a detailed description of the used materials is made, using the concepts that were previously taught in theoretical classes.…”
Section: Introductionmentioning
confidence: 99%